Comprehensive Analysis of the Expression and Prognosis for the DREAM Complex in Human Cancers - Wang, Lulu; Liu, Xiaowei (Frontiers in Genetics, 2022)
The DREAM complex is an evolutionarily conserved cell cycle regulating multi-protein complex. In addition to playing an essential function in the cell cycle, it also plays a vital role in various survival activities. Accumulating evidence suggests that DREAM complex plays a crucial role in oncogenesis. However, the regulatory mechanism of DREAM complex in cancer remains unclear. This study used multi-omics data from Cancer Genome Atlas and Cancer Cell Line Encyclopedia to comprehensively identify DREAM complex in tumor samples from 33 cancer types. Our analysis showed that the foremost common kind of DREAM complex gene mutation is a missense mutation in the genome landscape. Expression analysis showed that the expression of methylation-mediated DREAM complex was down-regulated. In addition, we found that the expression of the DREAM complex can be performed to predict the survival of various cancer patients. Pathway analysis showed that the DREAM complex is related to apoptosis inhibition, cell cycle, DNA damage response, RAS/MAPK, and RTK signaling pathway activation. Importantly, we have discovered some potential drugs that may target the DREAM complex. In summary, this study revealed the genomic changes and clinical features of the DREAM complex in 33 cancers, which may also provide new insights for cancer treatment and may offer alternative options for the treatment of clinically refractory cancers.